Analysis of high voltage-gain hybrid DC-DC power converter with RBFN based MPPT for renewable photovoltaic applications - Kumar K.; Tiwari R.; Babu N.R.; Padmanaban S.; Bhaskar M.S.; Ramachandaramurthy V.K. (Institute of Electrical and Electronics Engineers Inc., 2023)
Electric inverters; Energy conversion; Gain measurement; HVDC power transmission; Maximum power point trackers; Natural resources; Neural networks; Renewable energy resources; DC-DC Boost Converterr; High voltage gain; Maximum power; Photovoltaic; Photovoltaic applications; Renewable energy source; Voltage gain; Voltage levels; DC-DC converters